Microbial respiration with chlorine oxyanions: diversity and physiological and biochemical properties of chlorate‐ and perchlorate‐reducing microorganisms. Issue 1 (23rd June 2015) - Liebensteiner, Martin G.; Oosterkamp, Margreet J.; Stams, Alfons J.M.
Abstract : Chlorine oxyanions are valuable electron acceptors for microorganisms. Recent findings have shed light on the natural formation of chlorine oxyanions in the environment. These suggest a permanent introduction of respective compounds on Earth, long before their anthropogenic manufacture. Microorganisms that are able to grow by the reduction of chlorate and perchlorate are affiliated with phylogenetically diverse lineages, spanning from the Proteobacteria to the Firmicutes and archaeal microorganisms. Microbial reduction of chlorine oxyanions can be found in diverse environments and different environmental conditions (temperature, salinities, pH). It commonly involves the enzymes perchlorate reductase (Pcr) or chlorate reductase (Clr) and chlorite dismutase (Cld). Horizontal gene transfer seems to play an important role for the acquisition of functional genes. Novel and efficient Clds were isolated from microorganisms incapable of growing on chlorine oxyanions. Archaea seem to use a periplasmic Nar‐type reductase (pNar) for perchlorate reduction and lack a functional Cld. Chlorite is possibly eliminated by alternative (abiotic) reactions. This was already demonstrated for Archaeoglobus fulgidus, which uses reduced sulfur compounds to detoxify chlorite. A broad biochemical diversity of the trait, its environmental dispersal, and the occurrence of relevant enzymes in diverse lineages may indicate early adaptations of life toward chlorine oxyanions on Earth.